Urgensi Spiritualitas dalam Dunia Pendidikan Perspektif Al-Ghazali - Abdur Rofik (LPPI Universitas Al-Qolam Malang, 2025)
The moral crisis in modern education indicates that intellectual intelligence alone is insufficient to shape a complete human personality. In this context, spirituality becomes a fundamental aspect that must be emphasized to prevent education from losing its ethical foundation. This study aims to examine Imam Al-Ghazali’s concept of spirituality and its significance in the educational sphere. Using a qualitative descriptive approach, this research draws upon a literature review of Al-Ghazali’s works such as Ihya’ Ulum al-Din, Bidayat al-Hidayah, and Mizan al-‘Amal. The findings reveal that Al-Ghazali regards spirituality as the core of human character formation. For him, education should not only convey knowledge but also purify the soul (tazkiyatun nafs) and cultivate divine awareness (ma’rifatullah). Spirituality plays a crucial role in harmonizing the intellect, emotions, and heart. When the educational system neglects this dimension, knowledge becomes logical yet morally empty. Therefore, spirituality should be internalized through religious habituation, ethical guidance, and moral formation. This concept remains relevant to foster knowledgeable individuals with strong moral responsibility. Keywords: Spirituality, Education, Al-Ghazali, Ethics, Morality